FLYPAPER EFFECT THEORY DALAM IMPLEMENTASI KEBIJAKAN DESENTRALISASI FISKAL - Suyanto, Suyanto (Universitas Muhammdaiyah Surakarta, 2010)
Fiscal decentralization can be considered as intergovernmental financial assistance within a state. This assistance is commonly called intergovernmental financial transfer that is transfer of fund from a level of government to another level. Generally, the transfer is usually occurred from a higher level of government the lower counterpart of a single state. The re- search is conducted to prove that Flypaper Effect has occurred in fiscal decentralization policy. The research finds that regional governments use the transfer for increasing their expenditures without raising the tax. The impact which is occurred from correlation of financial transfer by central government toward the income and expenditure of regional governments shows flypaper effect indication in the implementation of fiscal decentralization. In that case, the effect to the increase in regional expenditure is bigger than the effect toward its income. This is showing that transfer of the fund has caused the increase in vertical fiscal imbalance. Transfer of funds encourages the increase in the expenditure of autonomous regions.